Revisiting Pagurus pilosipes (Stimpson, 1858) (Crustacea: Decapoda: Anomura: Paguridae) - Komai, Tomoyuki; Yang, Chien-Hui; Okuno, Junji; Chan, Tin-Yam (Zootaxa, 2011)
The study of newly collected samples from Okinawa, Ryukyu Islands, revealed that males of Pagurus pilosipes (Stimpson, 1858) have a prominent right sexual tube directed posterolaterally. Comparison of specimens previously identified as Pagurus pilosipes and newly collected specimens, combined with a molecular genetic analysis using partial sequences of the mitochondrial cytochrome c oxidase I (COI) gene, shows that Stimpson’s taxon occurs in the Japanese mainland, the Ogasawara Islands, the Okinawa Islands, and Korea. Stimpson’s taxon is transferred to the genus Boninpagurus Asakura and Tachikawa, 2004. Based on morphological and molecular evidence, Boninpagurus acanthocheles Asakura & Tachikawa, 2004, the type species of Boninpagurus, is synonymized with B. pilosipes n. comb. Affinity of Boninpagurus is briefly discussed.